RETRACTED: Companies ESG transformation in the conditions of economy digitalization: From ESG to ESGP - Bicharov Ilia; Niyazbekova Shakizada; Semenov Alexander; Rozhkov Vladimir; Fadeeva Lyudmila; Irisheva Aigul; Bikashev Danat; Tsurova Lisa; Ugurchiev Omar (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001